The Humanization of Early Children Education - Made Saihu; Nasaruddin Umar (STAI Hubbulwathan Duri, 2021)
This study discusses the teaching-learning process seen from the humanistic education theory from Carl Ransom Rogers at Asmaul Husna Learning Park, South Jakarta. This paper focuses on the educational perspective's operation through fun learning techniques, integrated learning, and thematic learning. In this paper, the data sources are obtained through field observations and structured interviews from January to July 2019 using the case study method. Through the humanistic educational theory approach, this educational study is the importance of understanding the character and potential of early childhood to optimally develop children intellectual, emotional, and spiritual intelligence. Although sometimes some students are disobedient or lazy to take part in learning, teachers and institutional managers anticipate this by presenting information about child development. Even to a certain extent, the institution also includes parents to participate in learning activities together. Here is also the importance of a teacher's creativity in communicating, choosing parenting styles, and various other stimulations when carrying out the teaching and learning process in class and outside the classroom. Without teachers' creativity in teaching and learning, the improvement and enhancement of cognitive, affective, and psychomotor aspects will not be optimal. An educational perspective places the humanization aspect as the basis for transferring knowledge, transferring human values, and transferring happiness.